2001
DOI: 10.1074/jbc.m104278200
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Homologue in Rhabdomyosarcoma Functions as a Bifunctional Nuclear Receptor-interacting Protein with Both Coactivator and Corepressor Functions

Abstract: In a search for novel transcriptional intermediary factors for the estrogen receptor (ER), we used the ligandbinding domain and hinge region of ER as bait in a yeast two-hybrid screen of a cDNA library derived from tamoxifen-resistant MCF-7 human breast tumors from an in vivo athymic nude mouse model. Here we report the isolation and characterization of the forkhead homologue in rhabdomyosarcoma (FKHR), a recently described member of the hepatocyte nuclear factor 3/forkhead homeotic gene family, as a nuclear h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
145
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 50 publications
11
145
1
2
Order By: Relevance
“…In support of this it has recently been demonstrated that in human keratinocytes, FOXOs are essential for 11 of 115 immediate gene activation responses to TGFb (Gomis et al, 2006a). Taken together, these results suggest that (Nechamen et al, 2007) Hepatic nuclear factor-4 (HNF4) (Hirota et al, 2003) HOXA5 (Foucher et al, 2002 (Zhao et al, 2001) FOXO-binding partners KE van der Vos and PJ Coffer formation of a FOXO and Smad transcription factor complex is critical in the control of cell growth and proliferation, and that perturbation of the association or function of this complex could contribute to neoplasia.…”
Section: Integration Of Pi3k/foxo and Tgfb/smad Pathwayssupporting
confidence: 58%
See 1 more Smart Citation
“…In support of this it has recently been demonstrated that in human keratinocytes, FOXOs are essential for 11 of 115 immediate gene activation responses to TGFb (Gomis et al, 2006a). Taken together, these results suggest that (Nechamen et al, 2007) Hepatic nuclear factor-4 (HNF4) (Hirota et al, 2003) HOXA5 (Foucher et al, 2002 (Zhao et al, 2001) FOXO-binding partners KE van der Vos and PJ Coffer formation of a FOXO and Smad transcription factor complex is critical in the control of cell growth and proliferation, and that perturbation of the association or function of this complex could contribute to neoplasia.…”
Section: Integration Of Pi3k/foxo and Tgfb/smad Pathwayssupporting
confidence: 58%
“…Ablation of the ERa gene delays the onset of tumour development in mouse models, indicating that oestrogen receptor-mediated signalling indeed plays an important role in breast cancer (Bocchinfuso and Korach, 1997). FOXO1 was found to interact with ERa in a ligand-dependent manner, however there are conflicting reports as to the effect of this interaction on ER transcriptional activity (Schuur et al, 2001;Zhao et al, 2001). Schuur et al have also reported that ERa reciprocally repressed FOXO1-mediated promoter transactivation, while cell cycle arrest induced by FOXO1 in MCF7 cells was abrogated by estradiol (Schuur et al, 2001).…”
Section: Foxo Partners Regulating Muscle Homeostasismentioning
confidence: 99%
“…Nevertheless, other members of the FOX family, such as FOXO3a/FKHRL-1, do regulate ER-a gene transcription and interact with ER-a in the presence of beta estradiol. [25][26][27] The biological importance of an association with nuclear FOXP1 expression and ER-a positivity is that the nuclear receptor box in the FOXP1 protein may also enable it to act as a coregulator of ER-a.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interaction between FoxM and FoxO remains an intriguing prospect, and the equilibrium between proliferation and cell cycle arrest may be maintained in part by cooperation and interaction of these factors. For example, in addition to FoxObinding oestrogen receptor in breast cancer cells (Schuur et al, 2001;Zhao et al, 2001), which is critical in regulating the proliferation and differentiation of breast tissue, evidence suggests that FoxM1 and FoxO3a may cooperate to regulate ERa gene transcription .…”
Section: Foxo Transcriptional Network and Cell Cyclementioning
confidence: 99%